Modification of the Association Between T-Cell Immune Responses and Human Immunodeficiency Virus Type 1 Infection Risk by Vaccine-Induced Antibody Responses in the HVTN 505 Trial. (8th January 2018) - Fong, Youyi; Shen, Xiaoying; Ashley, Vicki C; Deal, Aaron; Seaton, Kelly E; Yu, Chenchen; Grant, Shannon P; Ferrari, Guido; deCamp, Allan C; Bailer, Robert T; Koup, Richard A; Montefiori, David; et al.
Abstract: Background: HVTN 505 was a human immunodeficiency virus type 1 (HIV-1) preventive vaccine efficacy trial of a DNA/recombinant adenovirus serotype 5 (rAd5) vaccine regimen. We assessed antibody responses measured 1 month after final vaccination (month 7) as correlates of HIV-1 acquisition risk. Methods: Binding antibody responses were quantified in serum samples from 25 primary endpoint vaccine cases (diagnosed with HIV-1 infection between month 7 and month 24) and 125 randomly sampled frequency-matched vaccine controls (HIV-1 negative at month 24). We prespecified for a primary analysis tier 6 antibody response biomarkers that measure immunoglobulin G (IgG) and immunoglobulin A (IgA) binding to Env proteins and 2 previously assessed T-cell response biomarkers. Results: Envelope-specific IgG responses were significantly correlated with decreased HIV-1 risk. Moreover, the interaction of IgG responses and Env-specific CD8 + T-cell polyfunctionality score had a highly significant association with HIV-1 risk after adjustment for multiple comparisons. Conclusions: Vaccinees with higher levels of Env IgG have significantly decreased HIV-1 risk when CD8 + T-cell responses are low. Moreover, vaccinees with high CD8 + T-cell responses generally have low risk, and those with low CD8 + T-cell and low Env antibody responses have high risk. These findings suggest the critical importance of inducing a robust IgG Env response when the CD8 + T-cell response is low. Abstract : Vaccine-elicited antibodies and T cells correlate with decreased human immunodeficiency virus type 1 (HIV-1) risk in an HIV-1 preventative vaccine efficacy trial of a DNA/recombinant adenovirus serotype 5 (rAd5) vaccine regimen.